Esensi Tuhan dan Manusia dalam Berkehendak dan Berbuat: Otoritas Kun Fayakun dan Sunnatullah - Rahmah, Jabal; Aderus, Andi; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The debate concerning the relationship between divine will and human freedom is a classic theme in Islamic thought that remains relevant to this day. On the one hand, Islam affirms the absoluteness of God’s will, as reflected in the concept of kun fayakun as a symbol of divine authority. On the other hand, the Qur’an also emphasizes human responsibility for actions and efforts through the principles of ikhtiar (human endeavor) and sunnatullah (divine laws). This study aims to critically examine the essence of God’s will and the position of human freedom from the perspective of Islamic thought, while positioning sunnatullah as a framework that bridges the two. This research employs a qualitative approach with a library research design, analyzing primary and secondary sources in the field of Islamic theology. The findings indicate that God’s will is absolute and unlimited, whereas human beings possess a limited yet accountable freedom. Sunnatullah functions as a divine law that enables humans to strive rationally without negating the supremacy of God’s will. Thus, the relationship between divine will and human freedom is complementary, in which human endeavor and divine decree mutually reinforce one another in shaping an ethical and meaningful life.